Pulmonary Hypertension Associated with Idiopathic Pulmonary Fibrosis: Current and Future Perspectives. (13th February 2017) - Collum, Scott D.; Amione-Guerra, Javier; Cruz-Solbes, Ana S.; DiFrancesco, Amara; Hernandez, Adriana M.; Hanmandlu, Ankit; Youker, Keith; Guha, Ashrith; Karmouty-Quintana, Harry
Abstract : Pulmonary hypertension (PH) is commonly present in patients with chronic lung diseases such as Chronic Obstructive Pulmonary Disease (COPD) or Idiopathic Pulmonary Fibrosis (IPF) where it is classified as Group III PH by the World Health Organization (WHO). PH has been identified to be present in as much as 40% of patients with COPD or IPF and it is considered as one of the principal predictors of mortality in patients with COPD or IPF. However, despite the prevalence and fatal consequences of PH in the setting of chronic lung diseases, there are limited therapies available for patients with Group III PH, with lung transplantation remaining as the most viable option. This highlights our need to enhance our understanding of the molecular mechanisms that lead to the development of Group III PH. In this review we have chosen to focus on the current understating of PH in IPF, we will revisit the main mediators that have been shown to play a role in the development of the disease. We will also discuss the experimental models available to study PH associated with lung fibrosis and address the role of the right ventricle in IPF. Finally we will summarize the current available treatment options for Group III PH outside of lung transplantation.